Learning to see and understand developing visual literacy. (Center of Humanities, 1973)
Explores works by Albers, Bonnard, Brueghel, Cassatt, Da Vinci, Goya, Hogarth, Lichtenstein, Magritte, Matisse, Moore, Picasso, Rosenquist, Steinberg, Tiepolo, Wyeth to show how artists have expressed their feelings in their work; plus photographs, posters, modern prints, sculpture, and mixed media pieces.